Effects of Heparin Oligosaccharides with High Affinity for Antithrombin III in Experimental Venous Thrombosis - Thomas, D P; Merton, Rosemary E; Barrowcliffe, T W; Thunberg, L; Lindahl, U (Thrombosis and Haemostasis, 1982)
The in vitro and in vivo characteristics of two oligosaccharide heparin fragments have been compared to those of unfractionated mucosal heparin. A decasaccharide fragment had essentially no activity by APTT or calcium thrombin time assays in vitro, but possessed very high specific activity by anti-Factor Xa assays. When injected into rabbits at doses of up to 80 ¼g/kg, this fragment was relatively ineffective in impairing stasis thrombosis despite producing high blood levels by anti-Xa assays. A 16-18 monosaccharide fragment had even higher specific activity (almost 2000 iu/mg) by chromogenic substrate anti-Xa assay, with minimal activity by APTT. When injected in vivo, this fragment gave low blood levels by APTT, very high anti-Xa levels, and was more effective in preventing thrombosis than the decasaccharide fragment. However, in comparison with unfractionated heparin, the 16-18 monosaccharide fragment was only partially effective in preventing thrombosis, despite producing much higher blood levels by anti-Xa assays.It is concluded that the high-affinity binding of a heparin fragment to antithrombin III does not by itself impair venous thrombogenesis, and that the anti-Factor Xa activity of heparin is only a partial expression of its therapeutic potential.
Keywords: Heparin; Oligosaccharides; Venous thrombosis